Fracture behavior of multiple adhesive postinstalled anchors subjected to shear force - Yuji Tajima; Kazuaki Hoki (Acta Polytechnica CTU Proceedings, 2022)
In this study, experiments were conducted on post-installed anchors subjected to shear force  in order to enhance applicability when post-installed anchors were used for seismic reinforcement. Furthermore, since there were a large number of post-installed anchors when they were actually used, an experiment was conducted in which aăshear force was simultaneously applied to one to four anchors. In this study, it was focused on number and pitch of anchors. Major findings of this study were summarized as follows: in case of 22.46 (N/mm2) for concrete compressive strength, shear strength of anchors was not double, triple, and quadruple as number of those increased to 2, 3, and 4, and that gradually decreased as number of those increased, the boundary condition between anchor shear rupture and pry-out failure was found that concrete compressive strength was 25.12 (N/mm2) or less and anchor pitch was 30 to 50 mm, and anchor was tensile strength over SD390.